A comparative study of Tualang honey spray versus film spray (OPSITE®) as post-long bone fracture fixation wound dressing - Shafei, Surianty; Sharifudin, Mohd Ariff; Ismail, Mohd Shukry; Ab Rahman, Shafuzain; Sadagatullah, Abdul Nawfar (2013)
Introduction: Honey-based dressings have a potential benefit in treating wounds in implant-related surgery due to its anti-microbial activities and healing potentials. The aim of the study is to compare Tualang honey spray with film spray (Opsite®) as an alternative dressing material following long bone fracture fixations. This is a preliminary study in Malaysia that involves human subjects.